(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the clinical symptoms of lumbar disc herniation according to modern medicine and traditional medicine. Research subjects and methods: A cross-sectional descriptive study was conducted on 93 patients with lumbar disc herniation at Thanh Nhan Hospital from October 2023 to April 2024. Results: The mean age was 51.2 ± 14.54; the male/female ratio was 1/1.16; the average VAS score was 5.62 ± 1.33 points; 100% of patients experiencing lumbar pain and limited spinal movement; magnetic resonance imaging shows the degree of hernia was mainly bulge and hernia, accounting for 84.9% and 43%. Posterior disc herniation accounts for the highest rate of 97.8%. According to the traditional medicine, 100% of patients belong to interior syndrome group, 98.9% of patients belong to asthenia with sthenia. The prevalence of cold syndrome was higher than heat syndrome. Blood stasis syndrome take the most percentage at 45.2%. Conclusion: This study significantly guides diagnosis, treatment, and disease assessment by integrating traditional and modern medicine approaches.